Design of Miniaturized Multiband Patch Antenna Using CSRR for WLAN/WiMAX Applications - Murtala Aminu Baba; Mohammad Kamal A Rahim; Farid Zubir; Mohd Fairus Mohd Yusoff (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
A novel miniaturized multiband, single-feed microstrip patch antenna is presented in this paper for WLAN and WiMAX applications. Both size reduction and multiband are obtained by etching the Multiple Complementary Split Ring Resonators (MC-SRR) on the ground plane of the normal patch antenna. At first, the normal patch antenna produces a single band of 5.15 GHz; 200 MHz (5.0500~5.2499). Subsequently, a Single Circular Split Ring Resonator (SC-SRR) is etched on the ground plane and produces a triple band of: 3.25 GHz; 288 MHz (3.1085~3.3964), 4.5 GHz; 101.3 MHz (4.4488~4.5501), and 5.22 GHz; 220 MHz (5.1191~5.3400) and Double Single Circular Split Ring Resonator (DC-MCSRR) with: 2.99 GHz; 60.7 MHz (2.9574~3.0181), 3.57 GHz; 324.7 MHz (3.4065~3.7312), and 5.1413 GHz; 115.4 MHz (5.0817~5.1971). The working bandwidths cover the desired frequency bands of WLAN 5.2 GHz and WiMAX 3.3/3.5 GHz. The proposed (MC-SRR) antenna can be employed to wireless communication systems due to its simplicity in design, compactness and miniaturization.